An evaluation of systematic tuberculosis screening at private facilities in Karachi, Pakistan. - Jacob Creswell; Saira Khowaja; Andrew Codlin; Rabia Hashmi; Erum Rasheed; Mubashir Khan; Irfan Durab; Christina Mergenthaler; Owais Hussain; Faisal Khan; Aamir J Khan (PLoS ONE)
Background In Pakistan, like many Asian countries, a large proportion of healthcare is provided through the private sector. We evaluated a systematic screening strategy to identify people with tuberculosis in private facilities in Karachi and assessed the approaches' ability to diagnose patients earlier in their disease progression. Methods and findings Lay workers at 89 private clinics and a large hospital outpatient department screened all attendees for tuberculosis using a mobile phone-based questionnaire during one year. The number needed to screen to detect a case of tuberculosis was calculated. To evaluate early diagnosis, we tested for differences in cough duration and smear grading by screening facility. 529,447 people were screened, 1,010 smear-positive tuberculosis cases were detected and 942 (93.3%) started treatment, representing 58.7% of all smear-positive cases notified in the intervention area. The number needed to screen to detect a smear-positive case was 124 (prevalence 806/100,000) at the hospital and 763 (prevalence 131/100,000) at the clinics; however, ten times the number of individuals were screened in clinics. People with smear-positive TB detected at the hospital were less likely to report cough lasting 2-3 weeks (RR 0.66 95%CI [0.49-0.90]) and more likely to report cough duration >3 weeks (RR 1.10 95%CI [1.03-1.18]). Smear-positive cases at the clinics were less likely to have a +3 grade (RR 0.76 95%CI [0.63-0.92]) and more likely to have +1 smear grade (RR 1.24 95%CI [1.02-1.51]). Conclusions Tuberculosis screening at private facilities is acceptable and can yield large numbers of previously undiagnosed cases. Screening at general practitioner clinics may find cases earlier than at hospitals although more people must be screened to identify a case of tuberculosis. Limitations include lack of culture testing, therefore underestimating true TB prevalence. Using more sensitive and specific screening and diagnostic tests such as chest x-ray and Xpert MTB/RIF may improve results.